Financial Distress in BUMN in Indonesia and Factors Affecting Financial Performance and Health Levels in BUMN Companies - Sridewi Nur Pasha; Nur Aisyah F Pulungan; Sugiyono Madelan (Fakultas Ekonomi Universitas Kadiri, 2023)
This research aims to determine whether there is Financial Distress in BUMN in Indonesia and State Equity Participation. The population in this study were state-owned and non-problematic infrastructure companies registered on the BUMN court website from 2016 to 2020. The sampling technique used was purposive sampling to obtain a sample of 12 companies—data analysis techniques using panel data regression analysis method. The study results show that Return On Equity (ROE) and Capital Expenditure is significant for financial distress. BUMN receives assistance from small and insignificant State Equity Participation (PMN) and is paid to pay off large debts based on the assignment Participation (PMN), Soundness Level of BUMN, Liquidity, and Leverage do not affect solving BUMN financial problems.